Characteristics, Biodiversity, and Cultivation Strategy of Low Nucleic Acid Content Bacteria - Hu, Wei; Zhang, Hui; Lin, Xiaowen; Liu, Ruidan; Bartlam, Mark; Wang, Yingying (Frontiers in Microbiology, 2022)
Low nucleic acid content (LNA) bacteria are ubiquitous and estimated to constitute 20% to 90% of the total bacterial community in marine and freshwater environment. LNA bacteria with unique physiological characteristics, including small cell size and small genomes, can pass through 0.45 μm filtration. The researchers proposed different terminologies for low nucleic acid content bacteria based on different research backgrounds, such as: filterable bacteria, oligotrophic bacteria and low-DNA bacteria. LNA bacteria have an extremely high level of genetic diversity and play an important role in material circulation in oligotrophic environment. However, the majority of LNA bacteria in the environment remain uncultivated. Thus, an important challenge now is to isolate more LNA bacteria from oligotrophic environments and gain insights into their unique metabolic mechanisms and ecological functions. Here, we reviewed LNA bacteria in aquatic environments, focusing on their characteristics, community structure and diversity, functions, and cultivation strategies. Exciting future prospects for LNA bacteria are also discussed.